Pipelay with Residual Curvature - Tewolde, Abraham (University of Stavanger, Norway, 2017)
Master's thesis in Offshore technology: Marine and subsea technology Offshore pipelines under operating loads, i.e. under high temperature and pressure, are exposed to expansion and compressive forces, which may cause the pipeline to buckle globally. If significant lateral motion and excessive feed-in occurs at a specific location, the pipeline may form a sharp twist of high curvature where the resulting strain may be very large to initiate structural failure. Commonly used mitigation measures in the offshore industry are by continuous burial or rock damping to avoid buckling of the pipeline completely; and by using various methods to trigger lateral buckling in a controlled and effective manner at a relatively low axial compressive force, for example snake lay, artificial vertical imperfections & buoyancy modules. These mitigation measures require the implementation of additional methods on the seabed, which often appear with significant cost. Recent developments have shown how the use of intermittent residual curvature sections during reel-lay installation of pipelines can be used to control global pipeline thermal buckling in the operational phase. The method was first implemented in Statoil’s Skuld project in the Norwegian sea in 2012. Results have shown that every section of the residual curvature is triggered as expected and ensured the sharing of thermal expansion. No additional methods were required to ensure the utilization within acceptable criteria. The method was found to be rewarding and cost effective than the above mentioned conventional mitigation methods. The residual curvature sections are created as under-straightened sections in the vertical plane at the straightener of the reel-lay vessel. These convex upward residual sections create an additional imperfection in the pipeline and lead to pipe roll as it moves through the under-bend due to reversed bending. If the RCM is to be used effectively as a means for lateral buckling control, the residual curvature sections should acquire a ...